Drivers of Exchange Rate Dynamics in Selected CIS Countries: Evidence from a Factor-Augmented Vector Autoregressive (FAVAR) Analysis - Christian Dreger; Jarko Fidrmuc (Emerging Markets Finance and Trade, 2011)
We investigate the likely sources of exchange rate dynamics in selected member countries of the Commonwealth of Independent States (CIS; Russia, Kazakhstan, Ukraine, Kyrgyzstan, Azerbaijan, and Moldova) over the past decade (1999-2010). Evidence is based on country VARs augmented by a regional common-factor structure (FAVAR model). The models include nominal exchange rates, the common factor of exchange rates in the CIS countries, and international drivers such as global trade, share prices, and oil price. Global, regional, and idiosyncratic shocks are identified in a standard Cholesky fashion. Their relevance for exchange rates is explored by a decomposition of the variance of forecast errors. The impact of global shocks on the development of exchange rates has increased, particularly if financial shocks are considered. Because of the recent global financial crisis, regional shocks have become more important at the expense of global shocks.
Additional information: This is an Accepted Manuscript of an article published by Taylor & Francis in Emerging Markets, Finance & Trade on 07 Dec 2014, available online: http://dx.doi.org/10.2753/REE1540-496X470403. This publication was produced as part of the FINESS project, funded by the European Commission through the 7th Framework Programme under contract no. 217266 (http://www.finess-web.eu/).; info:eu-repo/grantAgreement/EC/FP7/217266
Keywords: F31; C22; G15; 330; Exchange rates; CIS countries; financial crisis; FAVAR models